2004
DOI: 10.1002/chin.200445220
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiviral Activities of New Pyrazolo[4,3‐c]quinolin‐3‐ones and Their Ribonucleoside Derivatives.

Abstract: Synthesis and Antiviral Activities of New Pyrazolo[4,3-c]quinolin-3-ones andTheir Ribonucleoside Derivatives. -Several ribonucleoside derivatives of type (VI) and the corresponding heterocyclic bases (III) are synthesized and evaluated against vaccinia virus (VV) and herpes simplex virus type 1 (HSV-1). Derivatives (IIIa) and (IIIb) show modest inhibitory activity against VV. All compounds (III) show a modest inhibition of HSV-1. -(DE OLIVEIRA, M. R. P.; ALVES, T. R.; PINTO, A. C.; PEREIRA, H. D. S.; LEAO-FERR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…26 However, other studies showed that footpad thickness does not always reflect parasite burden and may be influenced by leukocyte infiltration at the infection site. 27,28 The anti-inflammatory effects on evolution of skin lesions and anti-Leishmania activity of pyrazole carbohydrazide derivatives should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…26 However, other studies showed that footpad thickness does not always reflect parasite burden and may be influenced by leukocyte infiltration at the infection site. 27,28 The anti-inflammatory effects on evolution of skin lesions and anti-Leishmania activity of pyrazole carbohydrazide derivatives should be investigated.…”
Section: Discussionmentioning
confidence: 99%